THE ROLE OF BRAF V600E IN THE DEVELOPMENT OF THYROID CANCER PHENOTYPE: A SYSTEMATIC REVIEW - Mega, Pratia; Aspitriani; Edi Poedjo Purnamawati, Ika Kartika; Krisna Murti (Fakultas Kedokteran Universitas Sriwijaya, 2025)
BRAF V600E mutation in thyroid cancer is of major concern because it is associated with increased tumor aggressiveness through the MAPK pathway activation that affects phenotypic characteristics such as morphology and tissue invasion patterns. The results of studies on the effects of this mutation often vary and are influenced by differences in study design and detection methods. This systematic review aims to clarify the relationship between BRAF V600E and phenotypic characteristics of PTC, as well as identify its clinical implications. This study method was a systematic literature review using the PRISMA method, and there were 8418 journals. After exclusion, 16 articles were found that met the research objectives. Based on the results, it was found that there was a relationship between BRAF V600E and thyroid cancer phenotypes such as female gender, older age at diagnosis, larger tumor size, histological subtypes, especially tall cell, higher nuclear score, capsule, extrathyroid, vascular, nerve invasion, lymph node metastasis, higher clinical stage, recurrence, and lower survival. However, there are other inconsistent studies regarding the association of BRAF V600E with these phenotype characteristics. BRAF V600E mutation significantly affects the phenotypic characteristics of thyroid cancer and is associated with several aggressive characteristics.